Amino acids and gut function - Wang, W. W; Qiao, S. Y; Li, D. F (Amino acids, 2009)
The intestine is not only critical for the absorption of nutrients, but also interacts with a complex external milieu. Most foreign antigens enter the body through the digestive tract. Dietary amino acids are major fuels for the small intestinal mucosa, as well as important substrates for syntheses of intestinal proteins, nitric oxide, polyamines, and other products with enormous biological importance. Recent studies support potential therapeutic roles for specific amino acids (including glutamine, glutamate, arginine, glycine, lysine, threonine, and sulfur-containing amino acids) in gut-related diseases. Results of these new lines of work indicate trophic and cytoprotective effects of amino acids on gut integrity, growth, and health in animals and humans.